1991
DOI: 10.1002/art.1780340704
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma levels of hyaluronate in patients with osteoarthritis and rheumatoid arthritis

Abstract: Plasma levels of hyaluronate (HA) in patients with rheumatoid arthritis (RA) and patients with osteoarthritis (OA), measured by enzyme‐linked immunosorbent assay, were compared with levels in a healthy, age‐matched non‐arthritic control group, in a retrospective study. Compared with the controls, the mean level of plasma HA was sevenfold higher in the RA group and twofold higher in the OA group. There was no statistically significant correlation between HA levels and 7 other clinical and biochemical parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(57 citation statements)
references
References 35 publications
(16 reference statements)
2
48
1
3
Order By: Relevance
“…54,55) It also has been reported that serum HA level was associated with the presence of radiographic knee OA. [56][57][58][59] It has been reported normal human the HA level in the ranged from 53.9 to 55.2 ng/mL. 60) In the present study, we used serum COMP and HA levels to evaluate these effects during CS therapy.…”
Section: )mentioning
confidence: 95%
“…54,55) It also has been reported that serum HA level was associated with the presence of radiographic knee OA. [56][57][58][59] It has been reported normal human the HA level in the ranged from 53.9 to 55.2 ng/mL. 60) In the present study, we used serum COMP and HA levels to evaluate these effects during CS therapy.…”
Section: )mentioning
confidence: 95%
“…Disease duration and presence or absence of knee effusion were recorded. Additionally, the presence of OAaffected joints was evaluated using an articular index, the numerical value of which is the sum of the total cartilage surface area (in cm 2 ) of each symptomatic joint as previously reported (34).…”
Section: Methodsmentioning
confidence: 99%
“…Serum HA levels have been reported to be elevated in patients with liver cirrhosis, cancers, rheumatoid arthritis, scleroderma, psoriasis and osteoarthritis [5][6][7][8]. Increased urine HA levels have been found in rheumatoid arthritis [1], cancers [9] and premature aging syndromes, including Werner's syndrome (WS) [10,11] and the Hutchinson-Gilford syndrome [12].…”
Section: Introductionmentioning
confidence: 99%